ECO-FRIENDLY RETORT FOR COCONUT SHELL CHARCOAL: TRAINING, PERFORMANCE TESTING, AND BUSINESS PROSPECTS - Zuliantoni, Zuliantoni; Supardi, Nurul Iman; Hardiansyah, Hardiansyah (Universitas Mataram, 2025)
This community service activity introduced retort technology as a more efficient and environmentally friendly alternative to traditional charcoal production methods. The training was conducted through theoretical presentations, tool demonstrations, and participatory field practice by members of the Pasar Kerkap Village Youth Organization. The main objective of this activity was to improve participants' knowledge and skills in sustainable charcoal production. A 10-item questionnaire was used to evaluate the success of 20 participants, covering technical knowledge, practical skills, and attitudes toward clean technology implementation. Data analysis was conducted descriptively using quantitative and qualitative approaches by comparing pre-test and post-test results. Technically, this activity targeted a 20% increase in charcoal yield, a 25% reduction in production time, and a reduction in smoke emissions during the combustion process. The training results showed a significant increase in participants' understanding of the safe and efficient working methods and procedures for operating retorts. Participants were able to operate the equipment according to the instructions and demonstrated a higher awareness of occupational safety and environmental impacts. Furthermore, they considered retort technology more fuel-efficient and easier to implement than conventional methods. Overall, this activity successfully achieved its objectives by providing appropriate technological solutions that have the potential to encourage local innovation and new business opportunities in the renewable energy sector